Impact of Positive Surgical Margins After Partial Nephrectomy - Carvalho, João André Mendes (Eur Urol Open Sci, 2020)
BACKGROUND: The impact of positive surgical margins (PSMs) after partial nephrectomy (PN) is controversial. OBJECTIVE: To evaluate the risk factors for a PSM and its impact on overall survival. DESIGN, SETTING, AND PARTICIPANTS: This is a retrospective study of 388 patients were submitted to PN between November 2005 and December 2016 in a single centre. Two groups were created: PSM and negative surgical margin (NSM) after PN. A p value of <0.05 was considered significant. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Relationships with outcome were assessed using univariable and multivariable tests and log-rank analysis. RESULTS AND LIMITATIONS: The PSM rate was 3.8% (N = 16). The mean age at the time of surgery (PSM group: 64.1 ± 11.3 vs NSM group: 61.8 ± 12.8 yr, p =  0.5) and the mean radiological tumour size (4.0 ± 1.5 vs 3.4 ± 1.8 cm, p =  0.2) were similar. Lesion location (p =  0.3), surgical approach (p =  0.4), warm ischaemia time (p =  0.9), and surgery time (p =  0.06) had no association with PSM. However, higher surgeon experience was associated with a lower PSM incidence (2.6% if ≥30 PNs vs 9.6% if <30 PNs; p =  0.02). Higher operative blood loss (p =  0.02), higher-risk tumours (p =  0.03), and larger pathological size (p =  0.05) were associated with an increase in PSM. In the PSM group, recurrence rate (18.7% vs 4.2%, p =  0.007) and secondary total nephrectomy rate (25% vs 4.4%, p <  0.001) were higher. However, overall survival was similar. Multivariate analysis revealed that high-risk tumour (p =  0.05) and low experience (p =  0.03) could predict a PSM. Limitations include retrospective design and reduced follow-up time. CONCLUSIONS: PSMs were mainly associated with high-risk pathological tumour (p =  0.05) and low-volume surgeon experience. Recurrence rate and need for total nephrectomy were higher in that group, but no impact on survival was noticed. PATIENT SUMMARY: The impact of positive surgical margins (PSMs) after partial nephrectomy is a matter of debate. In this study, we found that PSMs were mainly associated with aggressive disease and low surgeon experience.